Investigation and optimization of all-fiber based rare-earth-doped fiber lasers - Cheng, Xueping. (2011)
Rare-earth-doped fiber offers a wave guiding medium with which to produce very compact and extremely efficient active devices. During the past two decades, this concept has been investigated with different rare earth ions in both the silica and fluoride fibers. And continuing effort has led to the demonstration of a variety of highly efficient laser sources with improved performance. In this thesis, various types of all-fiber based rare-earth-doped fiber lasers had been investigated, designed and characterized. Firstly, I proposed two types of specialty all-fiber based ring lasers with novel fiber Bragg grating (FBG) designs. They were the single longitudinal mode fiber ring laser, and the single polarization fiber ring laser. My experimental results showed the agreement with theoretical prediction. Q-switching is an important technique for lasers to generate pulses with high peak power and pulse energy, which is desired for many applications. The numerical simulation is a vital approach for precisely characterize and optimize the Q-switched fiber laser. I introduced the travelling wave model for the Q-switched fiber laser simulation. Then based on this simulation model, I systemically analyzed and optimized the actively Q-switched fiber laser. I further developed the model with the consideration of the dynamics detuning processes FBG filters and comprehensive optimization work had been done to optimize the FBG-based Q-switched fiber laser.